2010
DOI: 10.1590/s0004-27302010000400010
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SMAD proteins, TGF-beta/activin signaling mediators, in human thyroid tissues

Abstract: Objective: To investigate the expression of SMAD proteins in human thyroid tissues since the inactivation of TGF-β/activin signaling components is reported in several types of cancer. Phosphorylated SMAD 2 and SMAD3 (pSMAD2/3) associated with the SMAD4 induce the signal transduction generated by TGF-β and activin, while SMAD7 inhibits this intracellular signaling. Although TGF-β and activin exert antiproliferative roles in thyroid follicular cells, thyroid tumors express high levels of these proteins. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 38 publications
8
33
1
3
Order By: Relevance
“…In this context, elevated expression of miR-146b-5p could be a key factor in thyroid cancer progression, decreasing SMAD4 levels to overcome the TGF-b inhibitory signal. We have previously shown that SMAD4 may be present in thyroid tumors (Matsuo et al, 2010), suggesting that other factors may be involved in thyroid tumorigenesis. Because the overexpression of inhibitory SMAD7 (SMAD7) has been reported in thyroid tumor samples and cell lines (Cerutti et al, 2003;Matsuo et al, 2010), regulation of the TGF-b pathway by SMAD7 and other regulatory proteins may also take part in the refractoriness to the TGF-b signal by thyroid tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, elevated expression of miR-146b-5p could be a key factor in thyroid cancer progression, decreasing SMAD4 levels to overcome the TGF-b inhibitory signal. We have previously shown that SMAD4 may be present in thyroid tumors (Matsuo et al, 2010), suggesting that other factors may be involved in thyroid tumorigenesis. Because the overexpression of inhibitory SMAD7 (SMAD7) has been reported in thyroid tumor samples and cell lines (Cerutti et al, 2003;Matsuo et al, 2010), regulation of the TGF-b pathway by SMAD7 and other regulatory proteins may also take part in the refractoriness to the TGF-b signal by thyroid tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that SMAD4 may be present in thyroid tumors (Matsuo et al, 2010), suggesting that other factors may be involved in thyroid tumorigenesis. Because the overexpression of inhibitory SMAD7 (SMAD7) has been reported in thyroid tumor samples and cell lines (Cerutti et al, 2003;Matsuo et al, 2010), regulation of the TGF-b pathway by SMAD7 and other regulatory proteins may also take part in the refractoriness to the TGF-b signal by thyroid tumor cells. Furthermore, crosstalk between the TGF-b signaling pathway and several other cancer-related pathways may contribute to the disruption of the TGF-b signal (Ellenrieder, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, some studies showed suppressive effect of TGF-β on thyroid cancer cell proliferation [15,16], whereas others resistance of thyroid cancers to TGF-β's anti-proliferative effect, at least partly due to miR-146b-5p mediated suppression of Smad4 expression [17], Smad4 mutations [18], elevated expression of Smad7 (an counterregulatory molecule of the canonical TGF-β signaling) [19], down-regulation of TβRII expression [20], etc. However, the recent studies showing overexpression of TGF-β in thyroid cancers of human and mouse origins [19,[21][22][23][24][25], particularly at their invasive fronts [22,23,25], strongly indicate involvement of TGF-β in invasion, metastasis and also epithelial-mesenchymal transition (EMT). From all these previous data as well as those with Tgfbr2 tpoKO mice in the current study, it can be concluded as follows; TGF-β does suppress proliferation of normal thyroid cells but is not strongly involved in tumor suppression by itself in the early carcinogenesis, and once thyroid cells transform, although some lose the responsiveness to TGF-β, TGF-β acts as a tumor promoter by promoting the aggressive phenotype (invasive and metastatic capabilities, and EMT phenotype) in the majority of thyroid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of activins' intracellular mediators (Smad) have also been reported in thyroid cells and in the nucleus of thyroid tumour cells, indicating propagation of activin signalling in thyrocytes [16].…”
Section: Introductionmentioning
confidence: 95%